HEPATITIS C VIRUS INFECTION IN PATIENTS WITH CHRONIC KDNEY DISEASE: A REVIEW - UMMATE I; NWANKWO E (Ntec Specialist, 2009)
Viral infections contribute greatly to the high global burden of chronic kidney disease (CKD) especially in parts of the world where the prevalence of glomerulonephritis is high. These infections pose special challenges in the management of patients throughout the spectrum of chronic kidney disease. Hepatitis C virus infection in patients with chronic kidney disease could be coincidental or be responsible for the CKD. The observance of universal principle against transmission of blood borne infections remain the single most effective tool to stop the tide of increasing HCV infections in CKD patients. Combination therapy using nucleoside analogue, ribavarin and interferons offers the only real chance of treating HCV infected patients.